Non-innocent adsorption of Co-pyrphyrin on rutile(110)1. Issue 35 (21st September 2015) - Gurdal, Yeliz; Luber, Sandra; Hutter, Jürg; Iannuzzi, Marcella
<x xml:space="preserve">Abstract</x> Co-pyrphyrin adsorbed on rutile(110) as a supported catalyst for water reduction.